Pembuatan Dudukan Pencekam Rem SS201 Sepeda Pancal Piringan 70 x 68 x 3 mm dengan Kapasitas 0,67 Biji per Jam - Akma Febriansya Sanjaya; Syamsul Hadi; Armada Putra Lespradana; Teguh Ariwibowo; Davin Auliya Rohman (Jurnal Kendali Teknik dan Sains, 2026)
The large number of modification orders for bicycle brake chuck holders, but rarely able to meet these needs is a problem faced in the field. The purpose of making is to obtain bicycle brake chuck holders from stainless steel, SS201 70x68 mm, 3 mm thick or according to modification orders. The manufacturing method includes: identification of consumer needs; design using Computer Aided Design (CAD) software; selection including purchasing of 3 mm thick SS201 plate material; cutting 72x72 mm SS201 plates, 3 mm thick with a shearing machine; marking for cutting shapes according to the design; cutting profiles with a cutting grinder into shapes according to the design and a tolerance of ± 0.3 mm, 3 mm thick; drilling 4 holes with a diameter of 9 mm at the location position according to the design; finishing; and product quality-dimensional inspection. The result of the manufacture is a bicycle brake clamp holder made of SS201 material, 70x68 mm, 3 mm thick with a manufacturing cost of Rp. 159,150,-/unit, and a manufacturing duration of 90 minutes, which means that the brake clamp holder can fulfill the function of placing the bicycle brake clamp and the modification needs of the customer.